Pengaruh Hubungan Corporate Governance Terhadap Kinerja Keuangan - Yudha Prawira; Haryanto Haryanto (Diponegoro Journal of Accounting, 2015)
This study examined the relationship of the Effect of Corporate Governance Financial Performance Against a case study on the financial company 'listed on the Stock Exchange in 2010-2012. The purpose of this study was to determine the effect of board size, the size of the independent directors, the size of the board of directors, managerial ownership on firm performance.The population in this study were all financial companies listed on the Jakarta Stock Exchange (JSX) during the study period, ie 2010-2012. The sample in this study sample of 198 companies.The results showed that the composition of the independent directors (having a positive influence on the performance of the company, the effect of board size positively on the performance of the company, the effect size of the board of directors is positively significant to the company's performance managerial ownership has a negative effect on the performance of the company.